Animals, Equality and Democracy - O'Sullivan, S. author. aut Link
XII, 213 p.
Keywords: Animals, Equality and Democracy examines the structure of animal protection legislation and finds that it is deeply inequitable, with a tendency to favour those animals the community is most likely to see and engage with. Siobhan O'Sullivan argues that these inequities violate fundamental principle of justice and transparency.